Five-year library development plan for Mountain State Agricultural College - Claravall, Nora J.; Atienza, Daisy B.; Gregorio, Leonor B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1978)
This study is a five-year library development plan designed for Mountain State Agricultural College. Its basic objective is to design an integrated library development plan for the Mountain State Agricultural College which will serve as an essential guide for the librarian and the administrators in preparing the library to assume its supportive role for the projected state university.
The study is initiated by a library assessment inventory, which includes an examination of existing records and documents related to Mountain State Agricultural College and the library, survey of the existing collection, staff and physical facilities, interviews with faculty members and administrative officials and the administration of a survey questionnaire through random sampling of students and faculty members.
The geographical setting of the institution; its physical features, area and people, climate and vegetation and natural resources are presented in Chapter II for background.
A historical sketch of the Mountain State Agricultural College; its resources, objectives and other programs are given in Chapter III. Likewise, the enrolment trends-past and projected, and the general control and organization of the college itself are included.
The following chapter relates the history of the Mountain State Agricultural College libraries and makes an assessment of the present status of the library. The library administration, personnel, budget, collection, physical facilities and services. Likewise included are the targets over a five-year period, strategies for the development projections and financial requirements.
In the last chapter, the findings of this study, and the recommendations for the implementation of the development plan are enumerated.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Mountain State Agricultural College. Library